Losing Afghanistan : an obituary for the intervention - Coburn, Noah (Stanford, California : Stanford University Press, 2016)
"The U.S.-led intervention in Afghanistan mobilized troops, funds, and people on an international level not seen since World War II. Hundreds of thousands of individuals and tens of billions of dollars flowed into the country. But what was gained for Afghanistan--or for the international community that footed the bill? Why did development money not lead to more development? Why did a military presence make things more dangerous? Through the stories of four individuals--an ambassador, a Navy SEAL, a young Afghan businessman, and a wind energy engineer--Noah Coburn weaves a vivid account of the challenges and contradictions of life during the intervention. Looking particularly at the communities around Bagram Airbase, this ethnography considers how Afghans viewed and attempted to use the intervention and how those at the base tried to understand the communities around them. These compelling stories step outside the tired paradigms of 'unruly' Afghan tribes, an effective Taliban resistance, and a corrupt Karzai government to show how the intervention became an entity unto itself, one doomed to collapse under the weight of its own bureaucracy and contradictory intentions"--Provided by publisher.
Surveying the intervention from above -- Intervening -- The exotic tribes of the intervention -- Before the invasion -- A new era? -- Contracting the intervention -- Climbing over the wall -- The merchant-warlord alternative -- Warlord density and its discontents -- How to host your own shura -- The pieces left behind.
Includes bibliographical references and index.
Print version record.
Keywords: Afghan War, 2001- -- Political aspects; Nation-building -- Afghanistan; Economic assistance -- Afghanistan; Afghanistan -- Politics and government -- 2001-; HISTORY -- Asia -- Central Asia; HISTORY -- Asia -- General; Buddhism and politics; Economic assistance; Nation-building.; Politics and government; Afghanistan; Electronic books